Effects of a novel poly (AA-co-AAm)/AlZnFe2O4/potassium humate superabsorbent hydrogel nanocomposite on water retention of sandy loam soil and wheat seedling growth - Shahid, Shaukat Ali; Qidwai, Ansar Ahmad; Anwar, Farooq; Ullah, Inam; Rashid, Umer (MDPI, 2012)
A novel poly(acrylic acid-co-acrylamide)AlZnFe2O4/potassium humate superabsorbent hydrogel nanocomposite (PHNC) was synthesized and its physical properties characterized using SEM, Energy Dispersive X-ray (EDX) and FTIR spectroscopic techniques. Air dried sandy loam soil was amended with 0.1 to 0.4 w/w% of PHNC to evaluate its soil moisture retention attributes. Effect of PHNC amendment on pH, electrical conductivity (EC), porosity, bulk density and hydraulic conductivity of sandy loam soil was also studied. The soil amendment with 0.1 to 0.4 w/w% of PHNC remarkably enhanced the moisture retention at field capacity as compared to the un-amended soils. Seed germination and seedling growth of wheat (Triticum aestivum L.) was considerably increased and a delay by 6–9 days in wilting of seedlings was observed in the soil amended with PHNC, resulting in improved wheat plant establishment and growth.